2017
DOI: 10.21580/jnsmr.2017.3.1.1697
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure Characterization of SiO2 from Petung Bamboo Leaf Ash (Dendrocalamus asper (Schult.f.) Backer ex Heyne)

Abstract: <p style="text-align: justify;">The Research about Synthesis and Characterization of SiO2 have been worked. We have synthesized Silica from “petung”bamboo leaf ash as SiO2 source. This step used sol gel methode. SiO2 were characterized by Fourier Transform Infra Red (FTIR) to investigated the stucture andX-Ray Diffaction to know about structure and crystallinity. FTIR spectra show peak at 617,22 cm-1 area that spesific for Si-H bond, peak at 786,96 cm-1and 1095,57 cm-1 area specific for Si-O-Si b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
1
1
Order By: Relevance
“…XRF showed that the silica contained in the ashes of petung bamboo (D. asper) leaves was 78.03%. This is not much different from the research conducted by Udaibah and Priyanto [38] which revealed that the silica content of petung bamboo leaf ash was 77.06%. The high silica content of petung bamboo leaf ash can be used as the main ingredient in the manufacture of petung bamboo leaf (D. asper) SCM.…”
Section: Results Of Petung Bamboo Leaf Analysis (D Asper) With Xrfcontrasting
confidence: 85%
“…XRF showed that the silica contained in the ashes of petung bamboo (D. asper) leaves was 78.03%. This is not much different from the research conducted by Udaibah and Priyanto [38] which revealed that the silica content of petung bamboo leaf ash was 77.06%. The high silica content of petung bamboo leaf ash can be used as the main ingredient in the manufacture of petung bamboo leaf (D. asper) SCM.…”
Section: Results Of Petung Bamboo Leaf Analysis (D Asper) With Xrfcontrasting
confidence: 85%
“…The formed gel was filtered then rinsed with hot water and oven dried until the mass was constant. The chemical reactions are as follows [12][13],…”
Section: Silica Recovery Process From Fly Ashmentioning
confidence: 99%